Differences in the Implementation of the 2013 Curriculum and the Independent Learning Curriculum at SMAN 3 Siak Hulu - Azita, Azita; Ersalianda, Dila; Andri, Mutiara; Mukhlis, Muhammad; Tandon, Meradith (Lingeduca: Journal of Language and Education Studies, 2023)
Curriculum is a series of plans and rules that include various elements such as objectives, content, methods, and evaluation of learning. The purpose of this study is to describe, analyze, interpret, and conclude the differences in the implementation of the 2013 curriculum and the independent curriculum at SMAN 3 Siak Hulu. The method used in this study is a quantitative method, collecting interview data. The research results obtained are 1) Differences in terms of objectives, the 2013 Curriculum integrates character education into subjects, while the Merdeka Curriculum emphasizes the growth of student character separately through character projects, 2) Strategy/method, the 2013 curriculum has not implemented differentiated learning, while The Merdeka Curriculum gives freedom to teachers to choose learning materials and use strategies that are appropriate to the conditions of their respective educational units, 3) Learning Materials, the 2013 Curriculum has material that is more dense and must be followed coherently, while the Merdeka Curriculum has material that is simpler and the teacher can choose which material will take precedence, 4) In terms of learning time allocation, both the 2013 Curriculum and the Merdeka Curriculum have a similar duration, 5) in terms of evaluation, the Merdeka Curriculum has evaluated the 2013 Curriculum, while the Merdeka Curriculum burdens the teacher in terms of preparation learning tools because it requires better differentiation than the 2013 Curriculum which has not yet done so, 6) Changes in Teacher Mindset and Perception: Implementation of the Independent Curriculum faces obstacles in the form of changes in mindset, perception, and paradigm of thinking of teachers regarding curriculum changes, and 7) The Independent Curriculum emphasizes education character, giving freedom to the teacher in choosing learning materials and strategies, as well as combining holistic assessments.